7 - Devolved Power: A Critical Interrogation of the Place, Roles and Obligations of the Media at the Grassroots in Kenya - Nyabuga, George (Africa Development, 2017)
The promulgation of a new Constitution in August 2010 opened a new chapter in Kenya’s political history. The constitution set in motion various actions, one of the most critical being the creation of county governments, effectively devolving power and attendant decision-making to the grassroots. Whilst the counties have faced myriad problems since the March 2013 general election, there is an overarching view that they have helped deliver political and economic goodies and development. The optimism is, however, dimming due to poor governance. Moreover, the media that is supposed to help advance transparency, accountability, constitutionalism and democracy seems emasculated due to various reasons including intolerance to press freedom, and the journalists’ inability and/or unwillingness to hold county governments and their leadership to account. This article critically examines the media’s coverage of the devolution process, and interrogates its capacity and efficacy in promoting accountability, constitutionalism and democracy at the county level in Kenya.